IMPLEMENTASI PSAK ETAP DALAM PENYUSUNAN LAPORAN KEUANGAN KUD SAWIT PERMAI - B41109063, Edino Yacob edino (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
EDINO YAKUBB41109063JURUSAN AKUNTANSIFAKULTAS EKONOMI UNIVERSITAS TANJUNGPURA ABSTRACT The aim of this research was to find out the implementation of Indonesian Financial Accounting Standarts For Non Publicly Accountable Entities (SAK ETAP) in preparing the financial statements of Sawit Permai Village Unit Coorperative.The method used in this study was a deskricriptive method which describes the data obtained from field research based on the actual facts of an object at the time of research in order to draw conclusions.The research findings indicated that the Sawit Permai Village Unit Cooperative had not fully applied the SAK ETAP as a guide in preparing its financial statements. The financial statements of Sawit Permai Village unit cooperative only presented profit and loss statement, balance sheet and cash flow statement. The factor that contributed the non existence of the SAK ETAP (2011) in the financial statements of the Sawit Permai Village Unit Cooperative was the employees’ lack of accounting competence and mastery in an effort to improve the guality of financial statements of the cooperative in accordance with SAK ETAP. Keywords: Financial Statement, SAK ETAP